Justification of intergroup violence – the role of right-wing authoritarianism and propensity for radical action. Issue 2 (4th May 2019) - Faragó, Laura; Kende, Anna; Krekó, Péter
ABSTRACT: Economic and political trends of the last decades resulted in a general rise in anti-minority populism in Hungary. Anti-minority sentiments have been manifested in violence primarily against the Roma, but also against other target groups. The aim of the current study is to reveal the social psychological mechanisms of justifying intergroup violence against outgroups representing a symbolic or a physical threat. Considering that right-wing authoritarianism (RWA) can legitimize violence agsainst threatening outgroups, we hypothesized that RWA would be more important in explaining justification of intergroup violence than a general propensity for radical action. We tested our hypothesis using computer-assisted personal interviews using a representative sample of 1000 respondents. Using structural equation modelling, we found that RWA was a much stronger predictor of the justification of intergroup violence against both physically and symbolically threatening groups than propensity for radical action. Furthermore, a comparison of the groups also revealed that those who justify violence against symbolically threatening groups were also higher in right-wing authoritarianism. These findings highlight that RWA justifies politically motivated aggression against different target groups in Hungary.